Peran Guru sebagai Role Model Digital: Strategi Penanaman Etika dan Tanggung Jawab Digital pada Generasi Z - Tahir Rohili (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The rapid advancement of digital technology requires teachers to serve not only as educators but also as digital role models for their students. This study aims to analyze the teacher’s role in instilling digital ethics and responsibility among Generation Z, as well as to identify effective strategies in shaping students’ digital character. A qualitative approach with a case study method was employed in several secondary schools in Lampung Province. Data were collected through observation, in-depth interviews, and documentation, and analyzed descriptively through data reduction, presentation, and conclusion drawing. The findings reveal that teachers play a central role in fostering digital ethics awareness through exemplary behavior, ethical communication, and digital responsibility habituation within the school environment. Teachers’ consistency in using social media, managing information, and engaging ethically in online interactions significantly influences students’ digital behavior. This study highlights the need to strengthen teachers’ digital literacy capacity based on moral and spiritual values. The implications suggest that educational policies should integrate the teacher’s role as a digital role model into the broader strategy for developing ethical and responsible digital citizens in the era of technological transformation.